Frameshift Variant in Novel Adenosine-A1-Receptor Homolog Associated With Bovine Spastic Syndrome/Late-Onset Bovine Spastic Paresis in Holstein Sires - Krull, Frederik; Hirschfeld, Marc; Wemheuer, Wilhelm Ewald; Brenig, Bertram (Frontiers in Genetics, 2020)
Since their first description almost 100 years ago, bovine spastic paresis (BSP) and bovine spastic syndrome (BSS) are assumed to be inherited neuronal-progressive diseases in cattle. Affected animals are characterized by (frequent) spasms primarily located in the hind limbs, accompanied by severe pain symptoms and reduced vigor, thus initiating premature slaughter or euthanasia. Due to the late onset of BSP and BSS and the massively decreased lifespan of modern cattle the importance of these diseases is underestimated. In the present study BSP/BSS affected German Holstein breeding sires from artificial insemination centers were collected and pedigree analysis, genome-wide association studies, whole genome resequencing, protein-protein-interaction network analysis and protein-homology modelling performed to elucidate the genetic background. The analysis of 46 affected and 213 control cattle revealed four significantly associated positions on chromosome 15 (BTA15), i.e. AC_000172.1:g.83465449A>G (-log10P = 19.17), AC_000172.1:g.81871849C>T (-log10P = 8.31) AC_000172.1:g.81872621A>T (-log10P = 6.81) and AC_000172.1:g.81872661G>C (-log10P = 6.42). Two additional loci were significantly associated located on BTA8 and BTA19, i.e. AC_000165.1:g.71177788T>C and AC_000176.1:g.30140977T>G, respectively. Whole genome resequencing of five affected individuals and six unaffected relatives (two fathers, two mothers, a half sibling and a full sibling) belonging to three different not directly related families was performed. After filtering, a homozygous loss of function variant was identified in the affected cattle, causing a frameshift in the so far unknown gene locus LOC100848076 encoding an adenosine-A1-receptor homologue. An allele frequency of the variant of 0.74 was determined in 3,093 samples of the 1000-bulls genome project.